Legal Certainty for Creditors on Subsidized Home Ownership Loan Collateral Based on Law Number 4 of 1996 Concerning Mortgage Rights - Maria Angelina Suwarsono; Ronny A. Maramis; Grace H. Tampongangoy (Transpublika Publisher, 2025)
Subsidized Mortgage (KPR) serves as a crucial government policy instrument aimed at fulfilling the housing needs of low-income communities. This financing scheme involves a credit agreement between banks and debtors, where the main collateral is secured through Mortgage Rights over land, formalized via a Deed of Granting Mortgage Rights (APHT). However, in practice, delays in executing APHT are common, prompting banks to initially use a Power of Attorney to Encumber Mortgage Rights (SKMHT). This practice raises concerns regarding legal certainty for creditors, especially when debtors default while the mortgage rights have not been formally registered. Such issues are reflected in the high rate of Non-Performing Loans (NPL) and unresolved certificate issuance cases. This research aims to analyze the legal regulation of collateral in Subsidized Mortgages based on Law Number 4 of 1996 concerning Mortgage Rights and to examine the juridical implications for creditors when guarantees have not been fully established. The study employs a normative legal research method with a juridical-normative approach, utilizing primary, secondary, and tertiary legal materials analyzed qualitatively through legal identification and doctrinal review. The findings indicate that while Mortgage Rights provide preferential legal standing for creditors, implementation challenges persist due to administrative inefficiencies, delays by Notaries or Land Deed Officials (PPAT), and complications from developers. Although the law grants time flexibility for SKMHT in subsidized mortgage schemes, it inadvertently creates potential legal uncertainty. Therefore, strengthening regulatory enforcement, expediting APHT processes, and enhancing oversight mechanisms are imperative to ensure legal certainty and protection for all stakeholders.